Budgetary processes in medical organizations under a global budget payment system - Cheng-Tsung Lu; Wen-Hsin Huang (Critical Public Health)
This study examines the budgetary process of medical organizations under a global budget payment system. Using questionnaire results from budgeting supervisors, four key effects are identified: the motivational effect of budgetary participation, the information effect of budgeting information system (BIS) characteristics, the cognitive effect of budget quality, and the performance effect of budget performance. The results reveal that high budgetary participation enhances BIS characteristics (i.e. control, communication, and forecasting), which in turn improve budget quality and performance. Furthermore, both environmental competition and unpredictability significantly impact budgetary participation, and unpredictability also augments BIS characteristics. This study proposes a theoretical fit model and provides insights for medical organizations’ budgetary practices.